1989
DOI: 10.1159/000125223
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inhibition of Hypothalamic-Pituitary-Ovarian Axis and Body Weight Gain by Brain-Directed Delivery of Estradiol-17β in Female Rats

Abstract: The effect of preferential delivery of estradiol (E2) into the brain on both the hypothalamic-pituitary-ovarian axis and weight gain was studied in female rats. When E2 was coupled to a lipoidal dihydropyridine-pyridinium carrier, the resulting carrier E2 complex (CE), upon a single intravenous administration to cycling female rats, caused a dose-dependent inhibition of ovulation which lasted 3 times longer than with uncoupled E2. The dose of CE that delayed ovulation for 4 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…In female rats, an increased number of apoptotic corpora lutea at ‡0.05 mg ethinylestradiol/kg in study B and an increased number of early stage follicles in both studies at 0.2 mg/kg was observed and might reflect inhibition of the hypothalamic-pituitary-ovarian axis (Sarkar et al 1989) and/or a direct estrogenic effect. Classical direct estrogenic effects on the uterus were observed.…”
Section: Discussionmentioning
confidence: 83%
“…In female rats, an increased number of apoptotic corpora lutea at ‡0.05 mg ethinylestradiol/kg in study B and an increased number of early stage follicles in both studies at 0.2 mg/kg was observed and might reflect inhibition of the hypothalamic-pituitary-ovarian axis (Sarkar et al 1989) and/or a direct estrogenic effect. Classical direct estrogenic effects on the uterus were observed.…”
Section: Discussionmentioning
confidence: 83%
“…injection of E 2 -CDS (3 mg/kg) suppressed LH secretion by 88%, 86%, and 66% relative to DMSO controls at 12, 18, and 24 days, respectively, and that E 2 levels were not elevated relative to the DMSO control at any sampling time [465]. A single i. v. administration of doses as low as 0.5 mg/kg to ovariectomized rats induced prolonged (3-6 weeks) pharmacological effects as measured by LH suppression [463,465,473], reduced rate of weight gain [466,[471][472][473], or, in castrated male rats, reestablishment of copulatory behavior [464]. A large number of other very encouraging results have been obtained in various animal models; most of them have been reviewed previously [33,340,475,476,478,484].…”
Section: Estradiol-cds Estradiol-cds (Estredoxmentioning
confidence: 93%
“…Since its first synthesis in 1986 [462], E 2 -CDS (194) has been investigated in several models [463][464][465][466][467][468][469][470][471][472][473][475][476][477][478][479][480][481][482]484]. In vitro studies with rat organ homogenates as the test matrix indicated half-lives of 156.6, 29.9, and 29.2 min for E 2 -CDS (T at the 17-position) in plasma, liver, and brain homogenates, respectively [462].…”
Section: Estradiol-cds Estradiol-cds (Estredoxmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogens might be one set of additional biologic and genetic risk factors that contribute to AN. The anorectic effects of estrogens have been noted for decades 46,47 and the estrogen receptor b (ERb) gene has shown associations with both AN and BN. 48,49 This gene is also located on chromosome 14, which was found to be in significant linkage with BN.…”
Section: Int J Eat Disord 37 S43-s48 2005mentioning
confidence: 99%